Effectiveness of Irrigation Water Conservation in Tomato Cultivation with the Addition of Cattle, Poultry or Goat Manure-Based Compost - Andriyani, Idah; Istiqomah, Nuril; Wahyuningsih, Sri; Lestari, Ning Puji (The Journal of Experimental Life Science, 2026)
Efficient use of irrigation water is essential because water availability often does not meet crop requirements. In response, compost application is a potential solution, as it improves soil structure and enhances water-retention capacity. Nevertheless, the water-binding capacity of compost varies depending on the source of animal manure. To address this, the study aimed to evaluate the effectiveness of compost made from cattle, poultry, and goat manure in improving water retention in Andosol soil and supporting tomato growth as a biological indicator. The study used Andosol soil mixed with compost at application rates of 25% (500 g), 50% (1000 g), and 75% (1500 g), along with a control without compost. A two-factor completely randomized design with three replications was applied, and measured parameters included moisture content, media weight, water-holding capacity, pH, plant height, and leaf number. Results showed that the treatment using 1500 g of goat manure compost combined with 500 g of Andosol soil produced the highest water-holding capacity, making it the most effective option for irrigation water conservation. In contrast, cattle manure compost yielded the best tomato growth and productivity. Overall, these findings demonstrate that selecting the appropriate manure-based compost can enhance soil water retention and improve irrigation efficiency.